ClinkNotes: Towards a Corpus-Based, Machine-Aided Programme of Translation Teaching - Zhu, Chunshen; Yip, Po-Ching (Meta, 2010)
This article presents a report on a pilot project designed to construct a platform for large-scale teaching of translation or bilingual training at tertiary level. The programme, ClinkNotes, has the potential of accommodating parallel corpora of any language pairs, although the primary data used in this project are in English and Chinese. The report begins with a brief overview of the development of corpus-based approach to translation studies in relation to that of translation teaching as a profession. It then proceeds to describe the actual design (i.e., the theoretical framework, the methodology of annotation, and the simple execution of the software programme), and how it helps to cater to the pressing needs of the profession. The prospects of further development of the programme are also discussed.